Collapsibility of Gypseous Soil Treated with Pectin-Biopolymer through Leaching - Ahmed H. Hussein; Farouk M. Muhauwiss; Riyadh A. Abdul-Jabbar (Journal of Engineering)
Gypsum reinforcement in dry soil provides activity resistance. It quickly becomes a source of danger in the conditions of partial and complete soaking of gypsum soil as a result of the dissolution of gypsum, which poses a great danger to the structures built on this soil. The danger increases when water flows through it and works to leach the soil, which leads to the loss of its mass by leaching gypsum. The soil is chemically and mechanically improved to enhance its geotechnical properties, but despite its great advantages in strengthening, it has significant negative effects on the ecosystem, so the use of environmentally friendly materials is essential. Pectin was selected as an improved biopolymer and added at three different contents (0.5, 1, and 2)% to create a soil mixture and at four different gypsum contents (10, 20, 40, and 62%) to evaluate the chemical and mechanical properties of the improved mixture. Develop an engineering model to leach the soil and pectin mixture. The results showed a significant decrease in CH and CP. values due to biogel encapsulation of soil particles and pore filling properties. The percentage decrease in the values of (CH) reaches (0.67, 73, 75, and 68%) for soils 1, 2, 3, and 4, respectively. After soil (1, 2, 3, and 4), CP values decreased in percent (0.63, 0.63, 0.65, and 0.7%). TDS decreased at a biopolymer content of 2% from 1050, 1200, 2200, and 2500 mg/ml to 320, 540, 468, and 570 mg/ml of soils 1, 2, 3, and 4, respectively.